Penentuan Masyarakat Penerima Bantuan Perbaikan Rumah di Kecamatan Siantar Barat Menggunakan Metode ELECTRE - Roulina Simarmata; Rahmat W Sembiring; Rafiqa Dewi; Anjar Wanto; Eva Desiana (Journal of Computer System and Informatics (JoSYC), 2020)
Home improvement assistance is a government program for disadvantaged people. Home improvement assistance program is one of the government's efforts as a form of concern related to the condition of the homes of underprivileged communities. Therefore the purpose of this study is to determine the recipient of housing improvement assistance in the West Siantar Subdistrict as a reference material for the Office of Spatial Planning and Settlements (Tarukim) of Pematangsiantar city in providing housing repair assistance to be on target. The DSS method used in this study is the Elimination Et Choix Traduisant La Realita (ELECTRE) method. The alternative data samples used were 5, which were obtained from the Pematangsiantar Tarukim Office. This study also uses 5 criteria, including: roof material conditions, floor conditions, wall conditions, Work and Bathroom ownership. Based on calculations, Alternative 2 (A002) on behalf of Mr. Wariman was chosen as the best. Therefore, Mr. Wariman's family home is a community that is entitled to receive housing repair assistance in the West Siantar sub-district